2012
DOI: 10.3390/en5072071
|View full text |Cite
|
Sign up to set email alerts
|

On Space-Time Resolution of Inflow Representations for Wind Turbine Loads Analysis

Abstract: Efficient spatial and temporal resolution of simulated inflow wind fields is important in order to represent wind turbine dynamics and derive load statistics for design. Using Fourier-based stochastic simulation of inflow turbulence, we first investigate loads for a utility-scale turbine in the neutral atmospheric boundary layer. Load statistics, spectra, and wavelet analysis representations for different space and time resolutions are compared. Next, large-eddy simulation (LES) is employed with space-time res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…a local peak in the spectrum at a frequency coincident with three times the frequency of the turbine. This effect has been modeled by Sørensen et al [43] and has also been observed in LES [44][45][46]. These studies mainly focus on events from seconds to minutes, while less studies focus on spectra obtained over longer timescales.…”
Section: Introductionmentioning
confidence: 63%
“…a local peak in the spectrum at a frequency coincident with three times the frequency of the turbine. This effect has been modeled by Sørensen et al [43] and has also been observed in LES [44][45][46]. These studies mainly focus on events from seconds to minutes, while less studies focus on spectra obtained over longer timescales.…”
Section: Introductionmentioning
confidence: 63%
“…They performed a detailed analysis of the turbulent kinetic energy (TKE) budget in the wakes that reveals an important effect of the incoming flow turbulence level on the magnitude and spatial distribution of the shear production and transport terms. Sim et al [18] studied the space-time resolution of inflow representations for wind turbine loads. They performed the analyses using Fourier-based stochastic simulation of inflow turbulence and investigated loads for a utility-scale turbine in the neutral ABL.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted before, the x axes represent frequency and the values are hidden to protect Siemens data confidentiality. It has been highlighted in several previous studies that frequencies that are lower than approximately 10 times the rotor rated speed (1P) contribute most to fatigue loads (up to 2 Hz for turbines with 1P = 0.2 Hz; see Sim et al, 2012;Bergami and Gaunaa, 2014), and so the range shown in the figures in this paper includes the frequencies most important for load analysis. The peaks representing the frequencies with the highest energy in each figure have been highlighted and labeled as A, B, C, etc., and the comparisons among FAST, BHawC, and the measurements presented in these figures are discussed relative to these peaks in the following paragraphs.…”
Section: Discussion Of Results In the Frequency Domainmentioning
confidence: 99%